Impact of Mass Flow Rate on Thermal Behavior of PCM-Based SWH during Charging Operations - Nadjib, Muhammad -; Wahyudi, Wahyudi; Santosa, Tito Hadji Agung; Febriansyah, Tegar Bagaskara (Universitas Muhammadiyah Yogyakarta, 2024)
Using phase change materials in solar water heaters presents an intriguing prospect due to their notable energy density and potential for substantial thermal energy storage capacity. In the context of active-type solar water heaters, careful consideration must be given to the water flow rate as a crucial parameter. This paper investigates the thermal dynamics of active-type solar water heaters equipped with phase change materials, examining variations in mass flow rate during the charging process. Indoor experiments utilized horizontal tanks, flat plate collectors, pumps, and solar simulators. Cylindrical capsules filled with paraffin wax were employed and arranged horizontally within the tank, while K-type thermocouples were utilized to monitor water and paraffin wax temperatures. Charging procedures were executed over 160 minutes with mass flow rate adjustments. Data analysis was performed to evaluate the system's thermal performance during charging. Results indicate higher mass flow rates correspond to increased instantaneous, cumulative heat storage, and charging efficiency. The mass flow rate notably affects the thermal efficiency of solar water heater systems incorporating phase change materials.